Impact of polypharmacy phenogroups on different heart failure phenotypes in patients with chronic heart failure: a retrospective examination of real-world cohort - Sukik, Aseel; Aboughalia, Ahmed Tarek; Said Wali, Abdul Haseeb; Al Radaideh, Amro; Elsayed, Omar Mohamed; Amer, Mohammed A.; Abuodeh, Joud Said; Adegboye, Oyelola A.; Elzouki, AbdelNaser; Danjuma, Mohammed Ibn-Mas‘ud (Frontiers in Pharmacology, 2025)
BackgroundPolypharmacy is a rising morbidity amongst patients with chronic heart failure (CHF), with reported prevalence ranging from 70% to 85%. While polypharmacy is essential for managing comorbid conditions, its exact impact on heart failure outcomes is still emerging. This study aims to examine the effects of different polypharmacy phenogroups on mortality and intensive care unit (ICU) admissions across various heart failure phenotypes.MethodsWe conducted a retrospective cross-sectional study involving 4,902 patients with chronic heart failure treated at Hamad Medical Corporation, Doha, Qatar, between January 2018 and January 2022. Patients were classified into three polypharmacy groups: no polypharmacy (0–4 medications), major polypharmacy (five to eight medications), and excessive polypharmacy (≥9 medications). Heart failure phenotypes were categorized based on ejection fraction (EF): reduced EF (HFrEF, <40%), mildly reduced EF (HFmrEF, 40%–49%), and preserved EF (HFpEF, ≥50%). The primary outcome was all-cause mortality, with secondary outcomes including intensive care unit (ICU) admissions.ResultsA cohort of 4,902 patients with chronic heart failure, with a mean age of 61.47 years (SD 15.99), was analyzed. Among them, 51.7% had heart failure with reduced ejection fraction (HFrEF), 16.2% had mildly reduced ejection fraction (HFmrEF), and 32% had preserved ejection fraction (HFpEF). Major polypharmacy due to guideline-directed medical therapy (GDMT), was associated with a significant improvement in survival. In patients with HFpEF, the hazard ratio (HR) for all-cause mortality was 0.62 (95% CI: 0.52-0.75, p < 0.001), while for HFmrEF, it was 0.70 (95% CI: 0.59-0.85, p = 0.001). Conversely, excessive polypharmacy involving non-heart failure medications, was linked to increased ICU admissions (odds ratio [OR]: 1.34, 95% CI: 1.10-1.62, p = 0.02). Cox proportional hazards models demonstrated that excessive polypharmacy was associated with a hazard ratio of 0.11 (95% CI: 0.05-0.23, p < 0.001) for all-cause mortality when the medications were primarily heart failure-specific.ConclusionIn patients with chronic Heart failure, guideline directed polypharmacy was associated with improved survival, particularly in HFpEF and HFmrEF phenotypes. However, non-heart failure-related polypharmacy is associated with worse outcomes including ICU admissions, necessitating need for targeted interventions for this group of patients.